Sensory Stimulation-Induced Astrocytic Calcium Signaling in Electrically Silent Ischemic Penumbra - Murmu, Reena P.; Fordsmann, Jonas C.; Cai, Changsi; Brazhe, Alexey; Thomsen, Kirsten J.; Lauritzen, Martin (Frontiers in Aging Neuroscience, 2019)
Middle cerebral artery occlusion (MCAO) induces ischemia characterized by a densely ischemic focus, and a less densely ischemic penumbral zone in which neurons and astrocytes display age-dependent dynamic variations in spontaneous Ca2+ activities. However, it is unknown whether penumbral nerve cells respond to sensory stimulation early after stroke onset, which is critical for understanding stimulation-induced stroke therapy. In this study, we investigated the ischemic penumbra’s capacity to respond to somatosensory input. We examined adult (3- to 4-month-old) and old (18- to 24-month-old) male mice at 2–4 hours after MCAO, using two-photon microscopy to record somatosensory stimulation-induced neuronal and astrocytic Ca2+ signals in the ischemic penumbra. In both adult and old mice, MCAO abolished spontaneous and stimulation-induced electrical activity in the penumbra, and strongly reduced stimulation-induced Ca2+ responses in neuronal somas (35–82%) and neuropil (92–100%) in the penumbra. In comparison, after stroke, stimulation-induced astrocytic Ca2+ responses in the penumbra were only moderately reduced (by 54–62%) in adult mice, and were even better preserved (reduced by 31–38%) in old mice. Our results suggest that somatosensory stimulation evokes astrocytic Ca2+ activity in the ischemic penumbra. We hypothesize that the relatively preserved excitability of astrocytes, most prominent in aged mice, may modulate protection from ischemic infarcts during early somatosensory activation of an ischemic cortical area. Future neuroprotective efforts in stroke may target spontaneous or stimulation-induced activity of astrocytes in the ischemic penumbra.